Hubungan Terpaan Pernyataan Kontroversial Anji Mengenai COVID-19 di Media Sosial dan Komunikasi Interpersonal Dalam Keluarga Terhadap Sikap Kedisiplinan Masyarakat Melaksanakan Protokol Kesehatan Pada Masa New Normal - Umi Nafiatul Udkhiyah; Joyo Nur Suryanto Gono (Interaksi Online, 2021)
This study aims to determine the relationship between exposure to Anji's controversial statement regarding COVID-19 on social media and interpersonal communication in the family with community discipline in implementing health protocols. This study uses quantitative research methods with an explanatory approach. The data collection technique used non-probability sampling with a sample of 50 respondents. The theory used is Information Integration Theory and Pragmatic Theory of Communication. Hypothesis testing uses Kendall's analysis and the results of hypothesis testing show a significance value for the variable. The exposure to Anji's statementregarding COVID-19 is 0.917 and the correlation coefficient is 0.01, so it means that there is no relationship between Anji's controversial statement exposure (X1) and the disciplined attitude of the community in implementing health protocols (Y) and the correlation is very low. While the results of hypothesis testing for interpersonal communication variables in the family show a significance value of 0.037 and a correlation coefficient of 0.228, so that it means that there is a relationship between interpersonal communication in the family (X2) and community discipline in implementing health protocols (Y) and the correlation is low.